Digital Web Desain Dalam Meningkatkan Pemasaran UMKM FJ Collection Pada Pengakplikasian Blogger Di Kota Padang - Mediani, Rahma; Putri, Selvia Rahmayanti Putri; Fandi, Sonia Sri Fandi; Sularno, Sularno; Riesa, Rafidola Mareta Riesa (CV. ITTC INDONESIA, 2023)
In the era of digital marketing, websites have certainly become an important essence for business people. That's why many business people, both large and MSMEs, are less competitive than business people who use digital technology. Even large companies that have been around for a long time could go bankrupt if they are not willing to pursue young business people. Here the role of websites for MSMEs becomes more important. Especially if the website used is a professional website so that it can compete on an equal footing with previously established large companies. Technology has continued to develop with the times. In terms of using the internet as a complementary part of human life activities, the internet has touched various groups of people as part of its users. One use is to use internet facilities as part of marketing media. The aim of this research is to obtain a special marketing web application for MSMEs by considering the soft-skill aspects of managers. The MSME data sample was taken in North Sulawesi province. The method used to obtain an overview of the soft-skill understanding of MSME actors is descriptive analysis based on respondent responses. The results obtained from the perception data of MSME actors showed that 85% of respondents were good. Based on this data, a marketing web application was created to be used by MSMEs.Kata Kunci : Manfaat Tujuan Web Desain.